Sistem Pakar Diagnosa Penyakit Disebabkan Rokok dengan Menggunakan Metode Forward Chaining - Kelvin Dino Prasetio; Iqbal Kamil Sireegar; Suparmadi Suparmadi (Universitas Budi Darma, 2022)
The high cost and takes a long time to consult with a lung specialist at the hospital and the diseases caused by smoking are classified as complaints that are dangerous for the continuation of the disease. So we need an expert system to adopt human knowledge to computers, so that computers can provide solutions like doctors can. This research uses qualitative research methods and is included in descriptive research. The method used in this study is the forward chaining method and the search method used is forward data tracing to find conclusions. Data collection techniques through interviews and literature study. This research uses PHP programming language with MySQL database. Based on the results of the comparison between literature studies and interviews, obtained 7 diseases caused by smoking along with their causes and solutions. With this research process, an expert knowledge system application will be produced to be able to diagnose for the treatment of the disease.